Garçons entr’eux : amour et sexualité entre garçons - Martens, Vladimir; Monheim, Myriam; Peltier, Nancy (Bruxelles: Ex Æquo, 2011)
"Vladimir Martens, Myriam Monheim, Nancy Peltier (red.) Fonds Suzan Daniel (FSD)"